SELECTION OF HIGH YIELD AND 1000 GRAINS WEIGHT WINTER BREAD WHEAT VARIETIES FOR THE SOUTHERN REGIONS - Dilmurodov Sherzod Dilmurodovich (Journal of new century innovations, 2024)
Abstract: One of the main requirements for winter bread wheat varieties is the yield index. The ever-increasing population is increasing the demand for new, more productive varieties. This article gives an opinion about the process of selection of varieties and varieties suitable for the southern regions of our republic, with high yield, high chlorophyll content in leaves, and large weight of 1000 grains. The yield of winter bread wheat, the high content of chlorophyll in the leaf, and the high weight of 1000 grains were selected and involved in practical selection work.